GPs Meet Rare Lung Disorders Task Force factsheet: pulmonary arterial hypertension - Galiè, Nazzareno (Breathe (Sheff), 2015)
ERS GPs Meet Rare Lung Disorders Task Force factsheet: pulmonary arterial hypertension http://ow.ly/RlcYz